Transendentale kritiek en negatiewe dialektiek: ’n vergelyking tussen Dooyeweerd en Adorno se samelewingskritiek - Snyman, Johan (Koers, 1995)
Transcendental critique and negative dialectics: a comparison between Dooyeweerd’s and Adorno’s social critique. Plato's allegory of the cave set a fashion for philosophy, i.e. to distinguish between appearance and reality. This fashion is still distinguishable in the work of two philosophers whose social critiques, at a first glance, are worlds apart: Herman Dooyeweerd of the Free University in Amsterdam, and Theodor Adorno o f the Johann Wolfgang Goethe University in Frankfurt. Upon a closer look, however, many similarities appear. Their diagnoses of Western society probes beneath the beguiling surface of scientific and technological progress to reveal serious tensions deeply embedded in Western culture. The question arises: how conscious are they of their own embeddedness in this cultural crisis? Dooyeweerd and Adorno are analysed on this issue, and the conclusion shows Dooyeweerd’s philosophy to suffer from an intellectual hybris, whereas Adorno’s is portrayed as burdened with a paralysing aestheticism. The result of this critical analysis of Dooyeweerd and Adorno is a suggestion to rehabilitate the tradition of Christian thinking as an ongoing debate between rival interpretations of the biblical message, which offers creative opportunities to respond to cultural crises and the suffering they entail.